Memories of Anne Frank : reflections of a childhood friend - Gold, Alison Leslie (New York : Scholastic, 1999)
Recounts the story of Hannah Goslar, a close friend of Anne Frank and one of the last to see her alive.
"Polaris"--P. facing t.p.
Reprint. Originally published: 1997.
890
Accelerated Reader AR
Keywords: Pick-Goslar, Hannah -- Juvenile literature; Frank, Anne, -- 1929-1945.; Pick-Goslar, Hannah; Jews -- Netherlands -- Amsterdam -- Biography; Holocaust, Jewish (1939-1945) -- Netherlands -- Amsterdam -- Personal narratives; Jews -- Netherlands -- Biography; Women -- Biography; Holocaust, Jewish (1939-1945) -- Netherlands -- Amsterdam; Amsterdam (Netherlands) -- Biography